A Study on p-Cyclic Orbital Geraghty type Contractions - L.Suresh, M.; Gunasekar, T.; Karpagam, S.; Zlatanov, B.; ., . (International Journal of Engineering and Technology, 2018)
Consider a metric space  and the non empty sub sets, of X. A map called p-cyclic orbital Geraghty type of contraction is introduced.  Convergence of a unique fixed point and a best proximity point for this map is obtained in a uniformly convex Banach space setting.  Also, this best proximity point is the unique periodic point of such a map.